2007
DOI: 10.1007/s11104-007-9226-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Ni2+ on growth of cowpea (Vigna unguiculata)

Abstract: Despite the importance of Ni-polluted soils throughout the world, comparatively little is known about the activity of Ni 2+ required to reduce plant growth and the effects that Ni 2+ toxicity has on the plant. Cowpea (Vigna unguiculata (L.) Walp. cv Caloona) was grown in dilute nutrient solutions to investigate the effect of Ni 2+ activity on shoot and root growth. A Ni 2+ activity of 1.4 μM was found to cause a 10 % reduction in the relative fresh mass of the root and shoots. The primary site of Ni 2+ toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 19 publications
4
20
0
1
Order By: Relevance
“…It is obvious that dry mass of plant organs decreased with increasing Ni concentration in external solution. Our results are consistent with earlier studies of various crops which have shown that higher levels of trace elements, including Ni, cause a significant reduction in dry mass and essential metabolites [20][21][22][23]. Figure 1 also shows some considerable differences between studied cultivars.…”
Section: Resultssupporting
confidence: 92%
“…It is obvious that dry mass of plant organs decreased with increasing Ni concentration in external solution. Our results are consistent with earlier studies of various crops which have shown that higher levels of trace elements, including Ni, cause a significant reduction in dry mass and essential metabolites [20][21][22][23]. Figure 1 also shows some considerable differences between studied cultivars.…”
Section: Resultssupporting
confidence: 92%
“…The results are consistent with earlier studies of various crops which have shown that higher levels of trace elements including Ni cause a significant reduction in growth parameters and other essential metabolites [11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…Soil contamination by lead may cause a variety of environmental disturbances and its high phytotoxicity is a major problem in cultivated areas [7][8][9]. Its transport by streaming water may also lead to the contamination of ground and surface waters.…”
Section: Introductionmentioning
confidence: 99%